Methods of physiotherapeutic management used in the treatment of secondary lymphoedema in the Holycross Cancer Centre in Kielce - Opuchlik, Anna; Biskup, Małgorzata; Włoch, Anna; Lipińska-Stańczak, Magdalena; Lipińska, Anna (Medical Studies/Studia Medyczne, 2014)
Lymphoedema is a serious problem in patients treated for malignant neoplasm. The removal of regional lymph nodes – lymphadenectomy – is an inherent consequence of the surgical treatment of malignant neoplasm of breasts, genitals, prostate, skin cancer, salivary glands cancer and many others. The basic methods of conservative treatment of this chronic disease include complex methods of physiotherapy. The aim of this study is to present the rules of rehabilitation of patients treated for lymphoedema, which have been adopted by the team of the Department of Rehabilitation in the Holycross Cancer Centre in Kielce. This paper presents complex methods of physiotherapeutic management and discusses their availability and practical application in Polish health care institutions.